Appraisal of women's participation and contributions to wood plank marketing in Nigeria: A review (Agriculture, Food, and Natural Resources Journal, 2024)
The participation of women in the economy is essential to the general advancement and empowerment of communities. The market for wood planks is one such industry with a lot of promise. Wood planks are an essential part of furniture manufacturing, building, and many other businesses. In Nigeria, the wood industry contributes a significant role in the country's economy by giving many people, especially women, opportunities for jobs and income prospects. Women play an important role in small businesses and the unorganized sector, but they are frequently ignored and undervalued in the marketing of wood planks. However, there is a growing awareness of the vital contributions women make to this sector and the unique perspectives they bring, leading to increased advocacy for gender inclusivity and support structures that can help women overcome these barriers. This review article adopts a qualitative approach to explore the extent of women’s involvement in Nigerian wood plank marketing, analyze the obstacles faced, and identify potential avenues for increasing their participation. Data gathered through a combination of secondary sources, peer-reviewed articles, industry reports, policy documents, and case studies, given a comprehensive overview of the current landscape. Hence, this offers a nuanced understanding of the opportunities and barriers for women in wood plank marketing and strategies for fostering inclusive economic growth. Encouraging sustainable development and lowering poverty rates, especially in developing nations like Nigeria, requires the economic empowerment of women.
Keywords: Empowerment; Marketing; Participation; Women; Wood plank